POLA KONSUMSI TAHU DAN TEMPE PADA KELUARGA PRASEJAHTERA (KASUS DI KELURAHAN WAY LUNIK KECAMATAN PANJANG BANDAR LAMPUNG) - Muhammad Reza Azhar; Wan Abbas Zakaria; Rabiatul Adawiyah (Lampung University, 2019)
This research aimed to know the pattern of tofu and tempe consumption, and factors that affected tofu and tempe consumption. The method used in this research was survay in which location was chosen purposively at Way Lunik village, Panjang Subdistrict, Bandar Lampung. This research employed 60 sample families, in which housewives saved as respondents. The data were taken in August 2017 and analyzed quantitatively by multiple linier regression and descriptive method. The result showed that the average of total consumption of tofu by underprivilage families was 2,017.50 grams/week or 288.21 grams/day, while for tempe was 1,296.50 grams/week or 185.21 grams/day. Underprivilage families ate tofu and tempe very often. Consumption purposes of tofu and tempe was for pleasure and habit in which processing use deep frying and being sauteed. Underprivilage families consumpted tofu and tempe by buying. Factors that affected on tofu consumption by underprivilage families were tofu price, chicken egg price, and number of family members; while factors that affected on tempe consumption by underprivilage families were salted fish price, chicken egg price, family income and the number of family members.Key words: consumption pattern, tempe, tofu, underprivilage families